2021
DOI: 10.1108/ejm-06-2020-0449
|View full text |Cite
|
Sign up to set email alerts
|

Executives with customer experience and firm performance in the B2B context

Abstract: Purpose This paper aims to examine the presence of an executive with customer experience (ECE) in a supplier firm’s top management team (TMT). The role of ECE presence remains understudied in the marketing literature. This study attempts to examine the relationship between ECE presence and firm performance. Design/methodology/approach This paper draws on the resource-based view of the firm and adopts a panel firm fixed effects estimator to test the proposed hypotheses. The empirical analysis uses a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 155 publications
(203 reference statements)
1
10
0
Order By: Relevance
“…This indicates that while CX management can be standardized, the perceptions of how these experiences are delivered might vary. This is in line with CX's suggested context-specific nature in both B2C (Maklan and Klaus, 2011) and B2B settings (Feng et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 88%
“…This indicates that while CX management can be standardized, the perceptions of how these experiences are delivered might vary. This is in line with CX's suggested context-specific nature in both B2C (Maklan and Klaus, 2011) and B2B settings (Feng et al, 2021).…”
Section: Theoretical Implicationssupporting
confidence: 88%
“…MSMEs face many challenges during their business processes, due to which their business objective is very oriented and differs from buyer to buyer. So, understating the customer (i.e., buyer) orientation and providing them with solutions could help suppliers generate a better buyer experience (Feng et al, 2021 ). In the buyer–supplier relationship, the buyers’ and suppliers’ roles and strategies for maintaining a fruitful relationship are well discussed in terms of operations in supply chain management literature.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the literature indicates the importance of buyer experience in success and improved firm performance (Adams et al, 2012 ; Feng et al, 2021 ). However, the literature review found that research on buyer experience assessment for sustainable buyer–supplier is shallow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firm age (AGE), the log of the number of years that a firm has established is also used as a control variable, as older firms tend to Ratio of sales to marketing expenses at time period t (in logarithm form) perform worse (Loderer and Waelchli, 2010). Next, log of number of employees (NEMP) as a measure of firm size to control for economies of scales (Feng et al, 2021). ROA is return on total assets, which measures the profitability of a firm in relation to its total assets.…”
Section: Methodsmentioning
confidence: 99%